Rerangka Konseptual Dalam Akuntansi - Nur Fitriana; Via Mustika Irawan; Della Apriliana; Putri Purnama Dewi; Rini Armaya (CV. ITTC INDONESIA, 2025)
The conceptual framework states the information needed to predict management arrangements, and does not combine it with the information needed to calculate the value of the entity's future net cash flows. Qualitative methods using library research were used in this research. Where research is carried out by collecting data or scientific writing by understanding, reviewing and examining library materials that have legal relevance to the main problem. The conceptual framework of accounting is an integrated system consisting of sub-sub systems, namely objectives and fundamental concepts that are interrelated. The conceptual framework aims to provide guidance in preparing and presenting financial reports. The conceptual framework explains that the concept of caution does not imply the need for asymmetry, such as recognizing assets rather than liabilities requires the need for more persuasive evidence. The conceptual framework balances faithful representation and relevance to provide useful information for users of financial statements.